2021
DOI: 10.3390/jof7070546
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Pneumocystis jirovecii in Hospitalized Children Less Than 3 Years of Age

Abstract: Few data are available in the literature regarding Pneumocystis jirovecii infection in children under 3 years old. This retrospective cohort study aimed to describe medically relevant information among them. All children under 3 years old treated in the same medical units from April 2014 to August 2020 and in whom a P. jirovecii evaluation was undertaken were enrolled in the study. A positive case was defined as a child presenting at least one positive PCR for P. jirovecii in a respiratory sample. Medically re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…A recent single-center study of hospitalized children (<3 years old) in France found that 11% (32/279) of them were infected with P. jirovecii , with the highest positivity rate found in children with cardiopulmonary pathologies (22%), followed by SCID (19%), hyaline membrane disease (16%), asthma (9%), and acute leukaemia (6%) [ 222 ]. Of the infected children, 40% were considered colonization cases while 56% had confirmed PCP, mainly associated with SCID and other congenital diseases.…”
Section: Immunodeficient Conditions and Risk Factors For Pcpmentioning
confidence: 99%
“…A recent single-center study of hospitalized children (<3 years old) in France found that 11% (32/279) of them were infected with P. jirovecii , with the highest positivity rate found in children with cardiopulmonary pathologies (22%), followed by SCID (19%), hyaline membrane disease (16%), asthma (9%), and acute leukaemia (6%) [ 222 ]. Of the infected children, 40% were considered colonization cases while 56% had confirmed PCP, mainly associated with SCID and other congenital diseases.…”
Section: Immunodeficient Conditions and Risk Factors For Pcpmentioning
confidence: 99%
“…To date, our patient's extensive immunologic testing has been negative, suggesting presence of a primary PJP infection without any underlying immunodeficiency. Though previous studies have identified presence of PJP by polymerase chain reaction testing in children hospitalized with respiratory tract infections, this is thought to represent past exposure or colonization alone 2 . In such cases of exposure in non‐immunosuppressed children, if symptoms are even present, they are generally self‐limited and resolve without treatment 3 …”
Section: Figurementioning
confidence: 99%